Search for supersymmetry in events with soft leptons, low jet multiplicity, and missing transverse energy in proton-proton collisions at s=8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; Ivanov, Andrew; et al. (My University, 2016)
Results are presented from a search for supersymmetric particles in scenarios with small mass splittings. The data sample corresponds to 19.7 fb-1 of proton-proton collisions recorded by the CMS experiment at s=8 TeV. The search targets top squark (t~) pair production in scenarios with mass differences ?m=m(t~)-m(?~10) below the W-boson mass and with top-squark decays in the four-body mode (t~?b???~10), where the neutralino (?~10) is assumed to be the lightest supersymmetric particle (LSP). The signature includes a high transverse momentum (pT) jet associated with initial-state radiation, one or two low-pT leptons, and significant missing transverse energy. The event yields observed in data are consistent with the expected background contributions from standard model processes. Limits are set on the cross section for top squark pair production as a function of the t~ and LSP masses. Assuming a 100% branching fraction for the four-body decay mode, top-squark masses below 316 GeV are excluded for ?m=25 GeV at 95% CL. The dilepton data are also interpreted under the assumption of chargino-neutralino production, with subsequent decays to sleptons or sneutrinos. Assuming a difference between the common ?~1+/?~20 mass and the LSP mass of 20 GeV and a ?-enriched decay scenario, masses in the range m(?~1+)<307 GeV are excluded at 95% CL. © 2016 The Author.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Woods, N. (2016). Search for supersymmetry in events with soft leptons, low jet multiplicity, and missing transverse energy in proton-proton collisions at s=8 TeV. Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 759, 9-35. doi:10.1016/j.physletb.2016.05.033
Additional Authors: Friedl, M.;Fruehwirth, R.;Ghete, V. M.;Hartl, C.;Hörmann, N.;Hrubec, J.;Jeitler, M.;Knünz, V.;König, A.;Krammer, M.;Krätschmer, I.;Liko, D.;Matsushita, T.;Mikulec, I.;Rabady, D.;Rahbaran, B.;Rohringer, H.;Schieck, J.;Schöfbeck, R.;Strauss, J.;Treberer-Treberspurg, W.;Waltenberger, W.;Wulz, C. E.;Mossolov, V.;Shumeiko, N.;Suarez Gonzalez, J.;Alderweireldt, S.;Cornelis, T.;De Wolf, E. A.;Janssen, X.;Knutsson, A.;Lauwers, J.;Luyckx, S.;Van De Klundert, M.;Van Haevermaet, H.;Van Mechelen, P.;Van Remortel, N.;Van Spilbeeck, A.;Abu Zeid, S.;Blekman, F.;D'Hondt, J.;Daci, N.;De Bruyn, I.;Deroover, K.;Heracleous, N.;Keaveney, J.;Lowette, S.;Moreels, L.;Olbrechts, A.;Python, Q.;Strom, D.;Tavernier, S.;Van Doninck, W.;Van Mulders, P.;Van Onsem, G. P.;Van Parijs, I.;Barria, P.;Brun, H.;Caillol, C.;Clerbaux, B.;De Lentdecker, G.;Fasanella, G.;Favart, L.;Grebenyuk, A.;Karapostoli, G.;Lenzi, T.;Léonard, A.;Maerschalk, T.;Marinov, A.;Perniè, L.;Randle-conde, A.;Reis, T.;Seva, T.;Vander Velde, C.;Vanlaer, P.;Yonamine, R.;Zenoni, F.;Zhang, F.;Beernaert, K.;Benucci, L.;Cimmino, A.;Crucy, S.;Dobur, D.;Fagot, A.;Garcia, G.;Gul, M.;McCartin, J.;Ocampo Rios, A. A.;Poyraz, D.;Ryckbosch, D.;Salva, S.;Sigamani, M.;Strobbe, N.;Tytgat, M.;Van Driessche, W.;Yazgan, E.;Zaganidis, N.;Basegmez, S.;Beluffi, C.;Bondu, O.;Brochet, S.;Bruno, G.;Caudron, A.;Ceard, L.;Da Silveira, G. G.;Delaere, C.;Favart, D.;Forthomme, L.;Giammanco, A.;Hollar, J.;Jafari, A.;Jez, P.;Komm, M.;Lemaitre, V.;Mertens, A.;Musich, M.;Nuttens, C.;Perrini, L.;Pin, A.;Piotrzkowski, K.;Popov, A.;Quertenmont, L.;Selvaggi, M.;Vidal Marono, M.;Beliy, N.;Hammad, G. H.;Aldá Júnior, W. L.;Alves, F. L.;Alves, G. A.;Brito, L.;Correa Martins Junior, M.;Hamer, M.;Hensel, C.;Mora Herrera, C.;Moraes, A.;Pol, M. E.;Rebello Teles, P.;Belchior Batista Das Chagas, E.;Carvalho, W.;Chinellato, J.;Custódio, A.;Da Costa, E. M.;De Jesus Damiao, D.;De Oliveira Martins, C.;Fonseca De Souza, S.;Huertas Guativa, L. M.;Malbouisson, H.;Matos Figueiredo, D.;Mundim, L.;Nogima, H.;Prado Da Silva, W. L.;Santoro, A.;Sznajder, A.;Tonelli Manganote, E. J.;Vilela Pereira, A.;Ahuja, S.;Bernardes, C. A.;De Souza Santos, A.;Dogra, S.;Fernandez Perez Tomei, T. R.;Gregores, E. M.;Mercadante, P. G.;Moon, C. S.;Novaes, S. F.;Padula, Sandra S.;Romero Abad, D.;Ruiz Vargas, J. C.;Aleksandrov, A.;Hadjiiska, R.;Iaydjiev, P.;Rodozov, M.;Stoykova, S.;Sultanov, G.;Vutova, M.;Dimitrov, A.;Glushkov, I.;Litov, L.;Pavlov, B.;Petkov, P.;Ahmad, M.;Bian, J. G.;Chen, G. M.;Chen, H. S.;Chen, M.;Cheng, T.;Du, R.;Jiang, C. H.;Plestina, R.;Romeo, F.;Shaheen, S. M.;Spiezia, A.;Tao, J.;Wang, C.;Wang, Z.;Zhang, H.;Asawatangtrakuldee, C.;Ban, Y.;Li, Q.;Liu, S.;Mao, Y.;Qian, S. J.;Wang, D.;Xu, Z.;Avila, C.;Cabrera, A.;Chaparro Sierra, L. F.;Florez, C.;Gomez, J. P.;Gomez Moreno, B.;Sanabria, J. C.;Godinovic, N.;Lelas, D.;Puljak, I.;Ribeiro Cipriano, P. M.;Antunovic, Z.;Kovac, M.;Brigljevic, V.;Kadija, K.;Luetic, J.;Micanovic, S.;Sudic, L.;Attikis, A.;Mavromanolakis, G.;Mousa, J.;Nicolaou, C.;Ptochos, F.;Razis, P. A.;Rykaczewski, H.;Bodlak, M.;Finger, M., Jr.;Finger, M., Jr.;Abdelalim, A. A.;Awad, A.;El Sawy, M.;Mahrous, A.;Radi, A.;Calpas, B.;Kadastik, M.;Murumaa, M.;Raidal, M.;Tiko, A.;Veelken, C.;Eerola, P.;Pekkanen, J.;Voutilainen, M.;Härkönen, J.;Karimäki, V.;Kinnunen, R.;Lampén, T.;Lassila-Perini, K.;Lehti, S.;Lindén, T.;Luukka, P.;Mäenpää, T.;Peltola, T.;Tuominen, E.;Tuominiemi, J.;Tuovinen, E.;Wendland, L.;Talvitie, J.;Tuuva, T.;Besancon, M.;Couderc, F.;Dejardin, M.;Denegri, D.;Fabbro, B.;Faure, J. L.;Favaro, C.;Ferri, F.;Ganjour, S.;Givernaud, A.;Gras, P.;Hamel de Monchenault, G.;Jarry, P.;Locci, E.;Machet, M.;Malcles, J.;Rander, J.;Rosowsky, A.;Titov, M.;Zghiche, A.;Antropov, I.;Baffioni, S.;Beaudette, F.;Busson, P.;Cadamuro, L.;Chapon, E.;Charlot, C.;Dahms, T.;Davignon, O.;Filipovic, N.;Florent, A.;Granier de Cassagnac, R.;Lisniak, S.;Mastrolorenzo, L.;Miné, P.;Naranjo, I. N.;Nguyen, M.;Ochando, C.;Ortona, G.;Paganini, P.;Pigard, P.;Regnard, S.;Salerno, R.;Sauvan, J. B.;Sirois, Y.;Strebler, T.;Yilmaz, Y.;Zabi, A.;Agram, J. L.;Andrea, J.;Aubin, A.;Bloch, D.;Brom, J. M.;Buttignol, M.;Chabert, E. C.;Chanon, N.;Collard, C.;Conte, E.;Coubez, X.;Fontaine, J. C.;Gelé, D.;Goerlach, U.;Goetzmann, C.;Le Bihan, A. C.;Merlin, J. A.;Skovpen, K.;Van Hove, P.;Gadrat, S.;Beauceron, S.;Bernet, C.;Boudoul, G.;Bouvier, E.;Carrillo Montoya, C. A.;Chierici, R.;Contardo, D.;Courbon, B.;Depasse, P.;El Mamouni, H.;Fan, J.;Fay, J.;Gascon, S.;Gouzevitch, M.;Ille, B.;Lagarde, F.;Laktineh, I. B.;Lethuillier, M.;Mirabito, L.;Pequegnot, A. L.;Perries, S.;Ruiz Alvarez, J. D.;Sabes, D.;Sgandurra, L.;Sordini, V.;Vander Donckt, M.;Verdier, P.;Viret, S.;Toriashvili, T.;Tsamalaidze, Z.;Autermann, C.;Beranek, S.;Edelhoff, M.;Feld, L.;Heister, A.;Kiesel, M. K.;Klein, K.;Lipinski, M.;Ostapchuk, A.;Preuten, M.;Raupach, F.;Schael, S.;Schulte, J. F.;Verlage, T.;Weber, H.;Wittmer, B.;Zhukov, V.;Ata, M.;Brodski, M.;Dietz-Laursonn, E.;Duchardt, D.;Endres, M.;Erdmann, M.;Erdweg, S.;Esch, T.;Fischer, R.;Güth, A.;Hebbeker, T.;Heidemann, C.;Hoepfner, K.;Klingebiel, D.;Knutzen, S.;Kreuzer, P.;Merschmeyer, M.;Meyer, A.;Millet, P.;Olschewski, M.;Padeken, K.;Papacz, P.;Pook, T.;Radziej, M.;Reithler, H.;Rieger, M.;Scheuch, F.;Sonnenschein, L.;Teyssier, D.;Thüer, S.;Cherepanov, V.;Erdogan, Y.;Flügge, G.;Geenen, H.;Geisler, M.;Hoehle, F.;Kargoll, B.;Kress, T.;Kuessel, Y.;Künsken, A.;Lingemann, J.;Nehrkorn, A.;Nowack, A.;Nugent, I. M.;Pistone, C.;Pooth, O.;Stahl, A.;Aldaya Martin, M.;Asin, I.;Bartosik, N.;Behnke, O.;Behrens, U.;Bell, A. J.;Borras, K.;Burgmeier, A.;Campbell, A.;Choudhury, S.;Costanza, F.;Diez Pardos, C.;Dolinska, G.;Dooling, S.;Dorland, T.;Eckerlin, G.;Eckstein, D.;Eichhorn, T.;Flucke, G.;Gallo, E.;Garay Garcia, J.;Geiser, A.;Gizhko, A.;Gunnellini, P.;Hauk, J.;Hempel, M.;Jung, H.;Kalogeropoulos, A.;Karacheban, O.;Kasemann, M.;Katsas, P.;Kieseler, J.;Kleinwort, C.;Korol, I.;Lange, W.;Leonard, J.;Lipka, K.;Lobanov, A.;Lohmann, W.;Mankel, R.;Marfin, I.;Melzer-Pellmann, I. A.;Meyer, A. B.;Mittag, G.;Mnich, J.;Mussgiller, A.;Naumann-Emme, S.;Nayak, A.;Ntomari, E.;Perrey, H.;Pitzl, D.;Placakyte, R.;Raspereza, A.;Roland, B.;Sahin, M.;Saxena, P.;Schoerner-Sadenius, T.;Schröder, M.;Seitz, C.;Spannagel, S.;Trippkewitz, K. D.;Walsh, R.;Wissing, C.;Blobel, V.;Centis Vignali, M.;Draeger, A. R.;Erfle, J.;Garutti, E.;Goebel, K.;Gonzalez, D.;Görner, M.;Haller, J.;Hoffmann, M.;Höing, R. S.;Junkes, A.;Klanner, R.;Kogler, R.;Lapsien, T.;Lenz, T.;Marchesini, I.;Marconi, D.;Meyer, M.;Nowatschin, D.;Ott, J.;Pantaleo, F.;Peiffer, T.;Perieanu, A.;Pietsch, N.;Poehlsen, J.;Rathjens, D.;Sander, C.;Schettler, H.;Schleper, P.;Schlieckau, E.;Schmidt, A.;Schwandt, J.;Sola, V.;Stadie, H.;Steinbrück, G.;Tholen, H.;Troendle, D.;Usai, E.;Vanelderen, L.;Vanhoefer, A.;Vormwald, B.;Akbiyik, M.;Barth, C.;Baus, C.;Berger, J.;Böser, C.;Butz, E.;Chwalek, T.;Colombo, F.;De Boer, W.;Descroix, A.;Dierlamm, A.;Fink, S.;Frensch, F.;Friese, R.;Giffels, M.;Gilbert, A.;Haitz, D.;Hartmann, F.;Heindl, S. M.;Husemann, U.;Katkov, I.;Kornmayer, A.;Lobelle Pardo, P.;Maier, B.;Mildner, H.;Mozer, M. U.;Müller, T.;Müller, Th;Plagge, M.;Quast, G.;Rabbertz, K.;Röcker, S.;Roscher, F.;Sieber, G.;Simonis, H. J.;Stober, F. M.;Ulrich, R.;Wagner-Kuhr, J.;Wayand, S.;Weber, M.;Weiler, T.;Wöhrmann, C.;Wolf, R.;Anagnostou, G.;Daskalakis, G.;Geralis, T.;Giakoumopoulou, V. A.;Kyriakis, A.;Loukas, D.;Psallidas, A.;Topsis-Giotis, I.;Agapitos, A.;Kesisoglou, S.;Panagiotou, A.;Saoulidou, N.;Tziaferi, E.;Evangelou, I.;Flouris, G.;Foudas, C.;Kokkas, P.;Loukas, N.;Manthos, N.;Papadopoulos, I.;Paradas, E.;Strologas, J.;Bencze, G.;Hajdu, C.;Hazi, A.;Hidas, P.;Horvath, D.;Sikler, F.;Veszpremi, V.;Vesztergombi, G.;Zsigmond, A. J.;Beni, N.;Czellar, S.;Karancsi, J.;Molnar, J.;Szillasi, Z.;Bartók, M.;Makovec, A.;Raics, P.;Trocsanyi, Z. L.;Ujvari, B.;Mal, P.;Mandal, K.;Sahoo, D. K.;Sahoo, N.;Swain, S. K.;Bansal, S.;Beri, S. B.;Bhatnagar, V.;Chawla, R.;Gupta, R.;Bhawandeep, U.;Kalsi, A. K.;Kaur, A.;Kaur, M.;Kumar, R.;Mehta, A.;Mittal, M.;Singh, J. B.;Walia, G.;Kumar, Ashok;Bhardwaj, A.;Choudhary, B. C.;Garg, R. B.;Kumar, A.;Malhotra, S.;Naimuddin, M.;Nishu, N.;Ranjan, K.;Sharma, R.;Sharma, V.;Bhattacharya, S.;Chatterjee, K.;Dey, S.;Dutta, S.;Jain, Sa;Majumdar, N.;Modak, A.;Mondal, K.;Mukherjee, S.;Mukhopadhyay, S.;Roy, A.;Roy, D.;Roy Chowdhury, S.;Sarkar, S.;Sharan, M.;Abdulsalam, A.;Chudasama, R.;Dutta, D.;Jha, V.;Kumar, V.;Mohanty, A. K.;Pant, L. M.;Shukla, P.;Topkar, A.;Aziz, T.;Banerjee, S.;Bhowmik, S.;Chatterjee, R. M.;Dewanjee, R. K.;Dugad, S.;Ganguly, S.;Ghosh, S.;Guchait, M.;Gurtu, A.;Kole, G.;Kumar, S.;Mahakud, B.;Maity, M.;Majumder, G.;Mazumdar, K.;Mitra, S.;Mohanty, G. B.;Parida, B.;Sarkar, T.;Sur, N.;Sutar, B.;Wickramage, N.;Chauhan, S.;Dube, S.;Sharma, S.;Bakhshiansohi, H.;Behnamian, H.;Etesami, S. M.;Fahim, A.;Goldouzian, R.;Khakzad, M.;Mohammadi Najafabadi, M.;Naseri, M.;Paktinat Mehdiabadi, S.;Rezaei Hosseinabadi, F.;Safarzadeh, B.;Zeinali, M.;Felcini, M.;Grunewald, M.;Abbrescia, M.;Calabria, C.;Caputo, C.;Colaleo, A.;Creanza, D.;Cristella, L.;De Filippis, N.;De Palma, M.;Fiore, L.;Iaselli, G.;Maggi, G.;Maggi, M.;Miniello, G.;My, S.;Nuzzo, S.;Pompili, A.;Pugliese, G.;Radogna, R.;Ranieri, A.;Selvaggi, G.;Silvestris, L.;Venditti, R.;Verwilligen, P.;Abbiendi, G.;Battilana, C.;Benvenuti, A. C.;Bonacorsi, D.;Braibant-Giacomelli, S.;Brigliadori, L.;Campanini, R.;Capiluppi, P.;Castro, A.;Cavallo, F. R.;Chhibra, S. S.;Codispoti, G.;Cuffiani, M.;Dallavalle, G. M.;Fabbri, F.;Fanfani, A.;Fasanella, D.;Giacomelli, P.;Grandi, C.;Guiducci, L.;Marcellini, S.;Masetti, G.;Montanari, A.;Navarria, F. L.;Perrotta, A.;Rossi, A. M.;Rovelli, T.;Siroli, G. P.;Tosi, N.;Travaglini, R.;Cappello, G.;Chiorboli, M.;Costa, S.;Di Mattia, A.;Giordano, F.;Potenza, R.;Tricomi, A.;Tuve, C.;Barbagli, G.;Ciulli, V.;Civinini, C.;D'Alessandro, R.;Focardi, E.;Gonzi, S.;Gori, V.;Lenzi, P.;Meschini, M.;Paoletti, S.;Sguazzoni, G.;Tropiano, A.;Viliani, L.;Benussi, L.;Bianco, S.;Fabbri, F.;Piccolo, D.;Primavera, F.;Calvelli, V.;Ferro, F.;Lo Vetere, M.;Monge, M. R.;Robutti, E.;Tosi, S.;Brianza, L.;Dinardo, M. E.;Fiorendi, S.;Gennai, S.;Gerosa, R.;Ghezzi, A.;Govoni, P.;Malvezzi, S.;Manzoni, R. A.;Marzocchi, B.;Menasce, D.;Moroni, L.;Paganoni, M.;Pedrini, D.;Ragazzi, S.;Redaelli, N.;Tabarelli de Fatis, T.;Buontempo, S.;Cavallo, N.;Di Guida, S.;Esposito, M.;Fabozzi, F.;Iorio, A. O. M.;Lanza, G.;Lista, L.;Meola, S.;Merola, M.;Paolucci, P.;Sciacca, C.;Thyssen, F.;Azzi, P.;Bacchetta, N.;Benato, L.;Bisello, D.;Boletti, A.;Carlin, R.;Checchia, P.;Dall'Osso, M.;Dorigo, T.;Dosselli, U.;Gasparini, F.;Gasparini, U.;Gozzelino, A.;Lacaprara, S.;Margoni, M.;Meneguzzo, A. T.;Passaseo, M.;Pazzini, J.;Pegoraro, M.;Pozzobon, N.;Ronchese, P.;Simonetto, F.;Torassa, E.;Tosi, M.;Vanini, S.;Zanetti, M.;Zotto, P.;Zucchetta, A.;Zumerle, G.;Braghieri, A.;Magnani, A.;Montagna, P.;Ratti, S. P.;Re, V.;Riccardi, C.;Salvini, P.;Vai, I.;Vitulo, P.;Alunni Solestizi, L.;Biasini, M.;Bilei, G. M.;Ciangottini, D.;Fanò, L.;Lariccia, P.;Mantovani, G.;Menichelli, M.;Saha, A.;Santocchia, A.;Androsov, K.;Azzurri, P.;Bagliesi, G.;Bernardini, J.;Boccali, T.;Castaldi, R.;Ciocci, M. A.;Dell'Orso, R.;Donato, S.;Fedi, G.;Foà, L.;Giassi, A.;Grippo, M. T.;Ligabue, F.;Lomtadze, T.;Martini, L.;Messineo, A.;Palla, F.;Rizzi, A.;Savoy-Navarro, A.;Serban, A. T.;Spagnolo, P.;Tenchini, R.;Tonelli, G.;Venturi, A.;Verdini, P. G.;Barone, L.;Cavallari, F.;D'Imperio, G.;Del Re, D.;Diemoz, M.;Gelli, S.;Jorda, C.;Longo, E.;Margaroli, F.;Meridiani, P.;Organtini, G.;Paramatti, R.;Preiato, F.;Rahatlou, S.;Rovelli, C.;Santanastasio, F.;Traczyk, P.;Amapane, N.;Arcidiacono, R.;Argiro, S.;Arneodo, M.;Bellan, R.;Biino, C.;Cartiglia, N.;Costa, M.;Covarelli, R.;Degano, A.;Demaria, N.;Finco, L.;Kiani, B.;Mariotti, C.;Maselli, S.;Migliore, E.;Monaco, V.;Monteil, E.;Obertino, M. M.;Pacher, L.;Pastrone, N.;Pelliccioni, M.;Pinna Angioni, G. L.;Ravera, F.;Romero, A.;Ruspa, M.;Sacchi, R.;Solano, A.;Staiano, A.;Tamponi, U.;Belforte, S.;Candelise, V.;Casarsa, M.;Cossutti, F.;Della Ricca, G.;Gobbo, B.;La Licata, C.;Marone, M.;Schizzi, A.;Zanetti, A.;Kropivnitskaya, A.;Nam, S. K.;Kim, D. H.;Kim, G. N.;Kim, M. S.;Kong, D. J.;Lee, S.;Oh, Y. D.;Sakharov, A.;Son, D. C.;Brochero Cifuentes, J. A.;Kim, H.;Kim, T. J.;Song, S.;Choi, S.;Go, Y.;Gyun, D.;Hong, B.;Jo, M.;Kim, H.;Kim, Y.;Lee, B.;Lee, K.;Lee, K. S.;Lee, S.;Park, S. K.;Roh, Y.;Yoo, H. D.;Choi, M.;Kim, H.;Kim, J. H.;Lee, J. S. H.;Park, I. C.;Ryu, G.;Ryu, M. S.;Choi, Y.;Goh, J.;Kim, D.;Kwon, E.;Lee, J.;Yu, I.;Juodagalvis, A.;Vaitkus, J.;Ahmed, I.;Ibrahim, Z. A.;Komaragiri, J. R.;Md Ali, M. A. B.;Mohamad Idris, F.;Wan Abdullah, W. A. T.;Yusli, M. N.;Casimiro Linares, E.;Castilla-Valdez, H.;De La Cruz-Burelo, E.;Heredia-De La Cruz, I.;Hernandez-Almada, A.;Lopez-Fernandez, R.;Sanchez-Hernandez, A.;Carrillo Moreno, S.;Vazquez Valencia, F.;Pedraza, I.;Salazar Ibarguen, H. A.;Morelos Pineda, A.;Krofcheck, D.;Butler, P. H.;Ahmad, A.;Ahmad, M.;Hassan, Q.;Hoorani, H. R.;Khan, W. A.;Khurshid, T.;Shoaib, M.;Bialkowska, H.;Bluj, M.;Boimska, B.;Frueboes, T.;Górski, M.;Kazana, M.;Nawrocki, K.;Romanowska-Rybinska, K.;Szleper, M.;Zalewski, P.;Brona, G.;Bunkowski, K.;Byszuk, A.;Doroba, K.;Kalinowski, A.;Konecki, M.;Krolikowski, J.;Misiura, M.;Olszewski, M.;Walczak, M.;Bargassa, P.;Beirão Da Cruz E Silva, C.;Di Francesco, A.;Faccioli, P.;Ferreira Parracho, P. G.;Gallinaro, M.;Leonardo, N.;Lloret Iglesias, L.;Nguyen, F.;Rodrigues Antunes, J.;Seixas, J.;Toldaiev, O.;Vadruccio, D.;Varela, J.;Vischia, P.;Afanasiev, S.;Bunin, P.;Gavrilenko, M.;Golutvin, I.;Gorbunov, I.;Kamenev, A.;Karjavin, V.;Konoplyanikov, V.;Lanev, A.;Malakhov, A.;Matveev, V.;Moisenz, P.;Palichik, V.;Perelygin, V.;Shmatov, S.;Shulha, S.;Skatchkov, N.;Smirnov, V.;Zarubin, A.;Golovtsov, V.;Ivanov, Y.;Kim, V.;Kuznetsova, E.;Levchenko, P.;Murzin, V.;Oreshkin, V.;Smirnov, I.;Sulimov, V.;Uvarov, L.;Vavilov, S.;Vorobyev, A.;Andreev, Yu;Dermenev, A.;Gninenko, S.;Golubev, N.;Karneyeu, A.;Kirsanov, M.;Krasnikov, N.;Pashenkov, A.;Tlisov, D.;Toropin, A.;Epshteyn, V.;Gavrilov, V.;Lychkovskaya, N.;Popov, V.;Pozdnyakov, I.;Safronov, G.;Spiridonov, A.;Vlasov, E.;Zhokin, A.;Bylinkin, A.;Andreev, V.;Azarkin, M.;Dremin, I.;Kirakosyan, M.;Leonidov, A.;Mesyats, G.;Rusakov, S. V.;Baskakov, A.;Belyaev, A.;Boos, E.;Dubinin, M.;Dudko, L.;Ershov, A.;Gribushin, A.;Klyukhin, V.;Kodolova, O.;Lokhtin, I.;Myagkov, I.;Obraztsov, S.;Petrushanko, S.;Savrin, V.;Snigirev, A.;Azhgirey, I.;Bayshev, I.;Bitioukov, S.;Kachanov, V.;Kalinin, A.;Konstantinov, D.;Krychkine, V.;Petrov, V.;Ryutin, R.;Sobol, A.;Tourtchanovitch, L.;Troshin, S.;Tyurin, N.;Uzunian, A.;Volkov, A.;Adzic, P.;Milosevic, J.;Rekovic, V.;Alcaraz Maestre, J.;Calvo, E.;Cerrada, M.;Chamizo Llatas, M.;Colino, N.;De La Cruz, B.;Delgado Peris, A.;Dom'nguez Vázquez, D.;Escalante Del Valle, A.;Fernandez Bedoya, C.;Fernández Ramos, J. P.;Flix, J.;Fouz, M. C.;Garcia-Abia, P.;Gonzalez Lopez, O.;Goy Lopez, S.;Hernandez, J. M.;Josa, M. I.;Navarro De Martino, E.;Pérez-Calero Yzquierdo, A.;Puerta Pelayo, J.;Quintario Olmeda, A.;Redondo, I.;Romero, L.;Santaolalla, J.;Soares, M. S.;Albajar, C.;de Trocóniz, J. F.;Missiroli, M.;Moran, D.;Cuevas, J.;Fernandez Menendez, J.;Folgueras, S.;Gonzalez Caballero, I.;Palencia Cortezon, E.;Vizan Garcia, J. M.;Cabrillo, I. J.;Calderon, A.;Castiñeiras De Saa, J. R.;De Castro Manzano, P.;Duarte Campderros, J.;Fernandez, M.;Garcia-Ferrero, J.;Gomez, G.;Lopez Virto, A.;Marco, J.;Marco, R.;Martinez Rivero, C.;Matorras, F.;Munoz Sanchez, F. J.;Piedra Gomez, J.;Rodrigo, T.;Rodr'guez-Marrero, A. Y.;Ruiz-Jimeno, A.;Scodellaro, L.;Trevisani, N.;Vila, I.;Vilar Cortabitarte, R.;Abbaneo, D.;Auffray, E.;Auzinger, G.;Bachtis, M.;Baillon, P.;Ball, A. H.;Barney, D.;Benaglia, A.;Bendavid, J.;Benhabib, L.;Benitez, J. F.;Berruti, G. M.;Bloch, P.;Bocci, A.;Bonato, A.;Botta, C.;Breuker, H.;Camporesi, T.;Castello, R.;Cerminara, G.;D'Alfonso, M.;d'Enterria, D.;Dabrowski, A.;Daponte, V.;David, A.;De Gruttola, M.;De Guio, F.;De Roeck, A.;De Visscher, S.;Di Marco, E.;Dobson, M.;Dordevic, M.;Dorney, B.;du Pree, T.;Dünser, M.;Dupont, N.;Elliott-Peisert, A.;Franzoni, G.;Funk, W.;Gigi, D.;Gill, K.;Giordano, D.;Girone, M.;Glege, F.;Guida, R.;Gundacker, S.;Guthoff, M.;Hammer, J.;Harris, P.;Hegeman, J.;Innocente, V.;Janot, P.;Kirschenmann, H.;Kortelainen, M. J.;Kousouris, K.;Krajczar, K.;Lecoq, P.;Lourenço, C.;Lucchini, M. T.;Magini, N.;Malgeri, L.;Mannelli, M.;Martelli, A.;Masetti, L.;Meijers, F.;Mersi, S.;Meschi, E.;Moortgat, F.;Morovic, S.;Mulders, M.;Nemallapudi, M. V.;Neugebauer, H.;Orfanelli, S.;Orsini, L.;Pape, L.;Perez, E.;Peruzzi, M.;Petrilli, A.;Petrucciani, G.;Pfeiffer, A.;Piparo, D.;Racz, A.;Rolandi, G.;Rovere, M.;Ruan, M.;Sakulin, H.;Schäfer, C.;Schwick, C.;Seidel, M.;Sharma, A.;Silva, P.;Simon, M.;Sphicas, P.;Steggemann, J.;Stieger, B.;Stoye, M.;Takahashi, Y.;Treille, D.;Triossi, A.;Tsirou, A.;Veres, G. I.;Wardle, N.;Wöhri, H. K.;Zagozdzinska, A.;Zeuner, W. D.;Bertl, W.;Deiters, K.;Erdmann, W.;Horisberger, R.;Ingram, Q.;Kaestli, H. C.;Kotlinski, D.;Langenegger, U.;Renker, D.;Rohe, T.;Bachmair, F.;Bäni, L.;Bianchini, L.;Casal, B.;Dissertori, G.;Dittmar, M.;Donegà, M.;Eller, P.;Grab, C.;Heidegger, C.;Hits, D.;Hoss, J.;Kasieczka, G.;Lustermann, W.;Mangano, B.;Marionneau, M.;Martinez Ruiz del Arbol, P.;Masciovecchio, M.;Meister, D.;Micheli, F.;Musella, P.;Nessi-Tedaldi, F.;Pandolfi, F.;Pata, J.;Pauss, F.;Perrozzi, L.;Quittnat, M.;Rossini, M.;Starodumov, A.;Takahashi, M.;Tavolaro, V. R.;Theofilatos, K.;Wallny, R.;Aarrestad, T. K.;Amsler, C.;Caminada, L.;Canelli, M. F.;Chiochia, V.;De Cosa, A.;Galloni, C.;Hinzmann, A.;Hreus, T.;Kilminster, B.;Lange, C.;Ngadiuba, J.;Pinna, D.;Robmann, P.;Ronga, F. J.;Salerno, D.;Yang, Y.;Cardaci, M.;Chen, K. H.;Doan, T. H.;Jain, Sh;Khurana, R.;Konyushikhin, M.;Kuo, C. M.;Lin, W.;Lu, Y. J.;Yu, S. S.;Kumar, Arun;Bartek, R.;Chang, P.;Chang, Y. H.;Chang, Y. W.;Chao, Y.;Chen, K. F.;Chen, P. H.;Dietz, C.;Fiori, F.;Grundler, U.;Hou, W. S.;Hsiung, Y.;Liu, Y. F.;Lu, R. S.;Miñano Moya, M.;Petrakou, E.;Tsai, J. f;Tzeng, Y. M.;Asavapibhop, B.;Kovitanggoon, K.;Singh, G.;Srimanobhas, N.;Suwonjandee, N.;Adiguzel, A.;Bakirci, M. N.;Demiroglu, Z. S.;Dozen, C.;Girgis, S.;Gokbulut, G.;Guler, Y.;Gurpinar, E.;Hos, I.;Kangal, E. E.;Kayis Topaksu, A.;Onengut, G.;Ozdemir, K.;Ozturk, S.;Sunar Cerci, D.;Tali, B.;Topakli, H.;Vergili, M.;Zorbilmez, C.;Akin, I. V.;Bilin, B.;Bilmis, S.;Isildak, B.;Karapinar, G.;Yalvac, M.;Zeyrek, M.;Gülmez, E.;Kaya, M.;Kaya, O.;Yetkin, E. A.;Yetkin, T.;Cakir, A.;Cankocak, K.;Sen, S.;Vardarli, F. I.;Grynyov, B.;Levchuk, L.;Sorokin, P.;Aggleton, R.;Ball, F.;Beck, L.;Brooke, J. J.;Clement, E.;Cussans, D.;Flacher, H.;Goldstein, J.;Grimes, M.;Heath, G. P.;Heath, H. F.;Jacob, J.;Kreczko, L.;Lucas, C.;Meng, Z.;Newbold, D. M.;Paramesvaran, S.;Poll, A.;Sakuma, T.;Seif El Nasr-storey, S.;Senkin, S.;Smith, D.;Smith, V. J.;Bell, K. W.;Belyaev, A.;Brew, C.;Brown, R. M.;Calligaris, L.;Cieri, D.;Cockerill, D. J. A.;Coughlan, J. A.;Harder, K.;Harper, S.;Olaiya, E.;Petyt, D.;Shepherd-Themistocleous, C. H.;Thea, A.;Tomalin, I. R.;Williams, T.;Womersley, W. J.;Worm, S. D.;Baber, M.;Bainbridge, R.;Buchmuller, O.;Bundock, A.;Burton, D.;Casasso, S.;Citron, M.;Colling, D.;Corpe, L.;Cripps, N.;Dauncey, P.;Davies, G.;De Wit, A.;Della Negra, M.;Dunne, P.;Elwood, A.;Ferguson, W.;Fulcher, J.;Futyan, D.;Hall, G.;Iles, G.;Kenzie, M.;Lane, R.;Lucas, R.;Lyons, L.;Magnan, A. M.;Malik, S.;Nash, J.;Nikitenko, A.;Pela, J.;Pesaresi, M.;Petridis, K.;Raymond, D. M.;Richards, A.;Rose, A.;Seez, C.;Tapper, A.;Uchida, K.;Vazquez Acosta, M.;Virdee, T.;Zenz, S. C.;Cole, J. E.;Hobson, P. R.;Khan, A.;Kyberd, P.;Leggat, D.;Leslie, D.;Reid, I. D.;Symonds, P.;Teodorescu, L.;Turner, M.;Borzou, A.;Call, K.;Dittmann, J.;Hatakeyama, K.;Liu, H.;Pastika, N.;Charaf, O.;Cooper, S. I.;Henderson, C.;Rumerio, P.;Arcaro, D.;Avetisyan, A.;Bose, T.;Fantasia, C.;Gastler, D.;Lawson, P.;Rankin, D.;Richardson, C.;Rohlf, J.;St. John, J.;Sulak, L.;Zou, D.;Alimena, J.;Berry, E.;Bhattacharya, S.;Cutts, D.;Dhingra, N.;Ferapontov, A.;Garabedian, A.;Hakala, J.;Heintz, U.;Laird, E.;Landsberg, G.;Mao, Z.;Narain, M.;Piperov, S.;Sagir, S.;Syarif, R.;Breedon, R.;Breto, G.;Calderon De La Barca Sanchez, M.;Chauhan, S.;Chertok, M.;Conway, J.;Conway, R.;Cox, P. T.;Erbacher, R.;Gardner, M.;Ko, W.;Lander, R.;Mulhearn, M.;Pellett, D.;Pilot, J.;Ricci-Tam, F.;Shalhout, S.;Smith, J.;Squires, M.;Stolp, D.;Tripathi, M.;Wilbur, S.;Yohay, R.;Cousins, R.;Everaerts, P.;Farrell, C.;Hauser, J.;Ignatenko, M.;Saltzberg, D.;Takasugi, E.;Valuev, V.;Weber, M.;Burt, K.;Clare, R.;Ellison, J.;Gary, J. W.;Hanson, G.;Heilman, J.;Ivova Paneva, M.;Jandir, P.;Kennedy, E.;Lacroix, F.;Long, O. R.;Luthra, A.;Malberti, M.;Olmedo Negrete, M.;Shrinivas, A.;Wei, H.;Wimpenny, S.;Yates, B. R.;Branson, J. G.;Cerati, G. B.;Cittolin, S.;D'Agnolo, R. T.;Derdzinski, M.;Holzner, A.;Kelley, R.;Klein, D.;Letts, J.;Macneill, I.;Olivito, D.;Padhi, S.;Pieri, M.;Sani, M.;Sharma, V.;Simon, S.;Tadel, M.;Vartak, A.;Wasserbaech, S.;Welke, C.;Würthwein, F.;Yagil, A.;Zevi Della Porta, G.;Bradmiller-Feld, J.;Campagnari, C.;Dishaw, A.;Dutta, V.;Flowers, K.;Franco Sevilla, M.;Geffert, P.;George, C.;Golf, F.;Gouskos, L.;Gran, J.;Incandela, J.;McColl, N.;Mullin, S. D.;Richman, J.;Stuart, D.;Suarez, I.;West, C.;Yoo, J.;Anderson, D.;Apresyan, A.;Bornheim, A.;Bunn, J.;Chen, Y.;Duarte, J.;Mott, A.;Newman, H. B.;Pena, C.;Pierini, M.;Spiropulu, M.;Vlimant, J. R.;Xie, S.;Zhu, R. Y.;Andrews, M. B.;Azzolini, V.;Calamba, A.;Carlson, B.;Ferguson, T.;Paulini, M.;Russ, J.;Sun, M.;Vogel, H.;Vorobiev, I.;Cumalat, J. P.;Ford, W. T.;Gaz, A.;Jensen, F.;Johnson, A.;Krohn, M.;Mulholland, T.;Nauenberg, U.;Stenson, K.;Wagner, S. R.;Alexander, J.;Chatterjee, A.;Chaves, J.;Chu, J.;Dittmer, S.;Eggert, N.;Mirman, N.;Nicolas Kaufman, G.;Patterson, J. R.;Rinkevicius, A.;Ryd, A.;Skinnari, L.;Soffi, L.;Sun, W.;Tan, S. M.;Teo, W. D.;Thom, J.;Thompson, J.;Tucker, J.;Weng, Y.;Wittich, P.;Abdullin, S.;Albrow, M.;Anderson, J.;Apollinari, G.;Banerjee, S.;Bauerdick, L. A. T.;Beretvas, A.;Berryhill, J.;Bhat, P. C.;Bolla, G.;Burkett, K.;Butler, J. N.;Cheung, H. W. K.;Chlebana, F.;Cihangir, S.;Elvira, V. D.;Fisk, I.;Freeman, J.;Gottschalk, E.;Gray, L.;Green, D.;Grünendahl, S.;Gutsche, O.;Hanlon, J.;Hare, D.;Harris, R. M.;Hasegawa, S.;Hirschauer, J.;Hu, Z.;Jindariani, S.;Johnson, M.;Joshi, U.;Jung, A. W.;Klima, B.;Kreis, B.;Kwan, S.;Lammel, S.;Linacre, J.;Lincoln, D.;Lipton, R.;Liu, T.;Lopes De Sá, R.;Lykken, J.;Maeshima, K.;Marraffino, J. M.;Martinez Outschoorn, V. I.;Maruyama, S.;Mason, D.;McBride, P.;Merkel, P.;Mishra, K.;Mrenna, S.;Nahn, S.;Newman-Holmes, C.;O'Dell, V.;Pedro, K.;Prokofyev, O.;Rakness, G.;Sexton-Kennedy, E.;Soha, A.;Spalding, W. J.;Spiegel, L.;Taylor, L.;Tkaczyk, S.;Tran, N. V.;Uplegger, L.;Vaandering, E. W.;Vernieri, C.;Verzocchi, M.;Vidal, R.;Weber, H. A.;Whitbeck, A.;Yang, F.;Acosta, D.;Avery, P.;Bortignon, P.;Bourilkov, D.;Carnes, A.;Carver, M.;Curry, D.;Das, S.;Di Giovanni, G. P.;Field, R. D.;Furic, I. K.;Gleyzer, S. V.;Hugon, J.;Konigsberg, J.;Korytov, A.;Low, J. F.;Ma, P.;Matchev, K.;Mei, H.;Milenovic, P.;Mitselmakher, G.;Rank, D.;Rossin, R.;Shchutska, L.;Snowball, M.;Sperka, D.;Terentyev, N.;Thomas, L.;Wang, J.;Wang, S.;Yelton, J.;Hewamanage, S.;Linn, S.;Markowitz, P.;Martinez, G.;Rodriguez, J. L.;Ackert, A.;Adams, J. R.;Adams, T.;Askew, A.;Bochenek, J.;Diamond, B.;Haas, J.;Hagopian, S.;Hagopian, V.;Johnson, K. F.;Khatiwada, A.;Prosper, H.;Weinberg, M.;Baarmand, M. M.;Bhopatkar, V.;Colafranceschi, S.;Hohlmann, M.;Kalakhety, H.;Noonan, D.;Roy, T.;Yumiceva, F.;Adams, M. R.;Apanasevich, L.;Berry, D.;Betts, R. R.;Bucinskaite, I.;Cavanaugh, R.;Evdokimov, O.;Gauthier, L.;Gerber, C. E.;Hofman, D. J.;Kurt, P.;O'Brien, C.;Sandoval Gonzalez, I. D.;Silkworth, C.;Turner, P.;Varelas, N.;Wu, Z.;Zakaria, M.;Bilki, B.;Clarida, W.;Dilsiz, K.;Durgut, S.;Gandrajula, R. P.;Haytmyradov, M.;Khristenko, V.;Merlo, J. P.;Mermerkaya, H.;Mestvirishvili, A.;Moeller, A.;Nachtman, J.;Ogul, H.;Onel, Y.;Ozok, F.;Penzo, A.;Snyder, C.;Tiras, E.;Wetzel, J.;Yi, K.;Anderson, I.;Barnett, B. A.;Blumenfeld, B.;Eminizer, N.;Fehling, D.;Feng, L.;Gritsan, A. V.;Maksimovic, P.;Martin, C.;Osherson, M.;Roskes, J.;Sady, A.;Sarica, U.;Swartz, M.;Xiao, M.;Xin, Y.;You, C.;Baringer, P.;Bean, A.;Benelli, G.;Bruner, C.;Kenny, R. P., III;Majumder, D.;Malek, M.;Murray, M.;Sanders, S.;Stringer, R.;Wang, Q.;Ivanov, A.;Kaadze, K.;Khalil, S.;Makouski, M.;Maravin, Y.;Mohammadi, A.;Saini, L. K.;Skhirtladze, N.;Toda, S.;Lange, D.;Rebassoo, F.;Wright, D.;Anelli, C.;Baden, A.;Baron, O.;Belloni, A.;Calvert, B.;Eno, S. C.;Ferraioli, C.;Gomez, J. A.;Hadley, N. J.;Jabeen, S.;Kellogg, R. G.;Kolberg, T.;Kunkle, J.;Lu, Y.;Mignerey, A. C.;Shin, Y. H.;Skuja, A.;Tonjes, M. B.;Tonwar, S. C.;Apyan, A.;Barbieri, R.;Baty, A.;Bierwagen, K.;Brandt, S.;Busza, W.;Cali, I. A.;Demiragli, Z.;Di Matteo, L.;Gomez Ceballos, G.;Goncharov, M.;Gulhan, D.;Iiyama, Y.;Innocenti, G. M.;Klute, M.;Kovalskyi, D.;Lai, Y. S.;Lee, Y. J.;Levin, A.;Luckey, P. D.;Marini, A. C.;McGinn, C.;Mironov, C.;Narayanan, S.;Niu, X.;Paus, C.;Ralph, D.;Roland, C.;Roland, G.;Salfeld-Nebgen, J.;Stephans, G. S. F.;Sumorok, K.;Varma, M.;Velicanu, D.;Veverka, J.;Wang, J.;Wang, T. W.;Wyslouch, B.;Yang, M.;Zhukova, V.;Dahmes, B.;Evans, A.;Finkel, A.;Gude, A.;Hansen, P.;Kalafut, S.;Kao, S. C.;Klapoetke, K.;Kubota, Y.;Lesko, Z.;Mans, J.;Nourbakhsh, S.;Ruckstuhl, N.;Rusack, R.;Tambe, N.;Turkewitz, J.;Acosta, J. G.;Oliveros, S.;Avdeeva, E.;Bloom, K.;Bose, S.;Claes, D. R.;Dominguez, A.;Fangmeier, C.;Gonzalez Suarez, R.;Kamalieddin, R.;Keller, J.;Knowlton, D.;Kravchenko, I.;Lazo-Flores, J.;Meier, F.;Monroy, J.;Ratnikov, F.;Siado, J. E.;Snow, G. R.;Alyari, M.;Dolen, J.;George, J.;Godshalk, A.;Harrington, C.;Iashvili, I.;Kaisen, J.;Kharchilava, A.;Kumar, A.;Rappoccio, S.;Roozbahani, B.;Alverson, G.;Barberis, E.;Baumgartel, D.;Chasco, M.;Hortiangtham, A.;Massironi, A.;Morse, D. M.;Nash, D.;Orimoto, T.;Teixeira De Lima, R.;Trocino, D.;Wang, R. J.;Wood, D.;Zhang, J.;Hahn, K. A.;Kubik, A.;Mucia, N.;Odell, N.;Pollack, B.;Pozdnyakov, A.;Schmitt, M.;Stoynev, S.;Sung, K.;Trovato, M.;Velasco, M.;Brinkerhoff, A.;Dev, N.;Hildreth, M.;Jessop, C.;Karmgard, D. J.;Kellams, N.;Lannon, K.;Lynch, S.;Marinelli, N.;Meng, F.;Mueller, C.;Musienko, Y.;Pearson, T.;Planer, M.;Reinsvold, A.;Ruchti, R.;Smith, G.;Taroni, S.;Valls, N.;Wayne, M.;Wolf, M.;Woodard, A.;Antonelli, L.;Brinson, J.;Bylsma, B.;Durkin, L. S.;Flowers, S.;Hart, A.;Hill, C.;Hughes, R.;Ji, W.;Kotov, K.;Ling, T. Y.;Liu, B.;Luo, W.;Puigh, D.;Rodenburg, M.;Winer, B. L.;Wulsin, H. W.;Driga, O.;Elmer, P.;Hardenbrook, J.;Hebda, P.;Koay, S. A.;Lujan, P.;Marlow, D.;Medvedeva, T.;Mooney, M.;Olsen, J.;Palmer, C.;Piroué, P.;Quan, X.;Saka, H.;Stickland, D.;Tully, C.;Werner, J. S.;Zuranski, A.;Malik, S.;Barnes, V. E.;Benedetti, D.;Bortoletto, D.;Gutay, L.;Jha, M. K.;Jones, M.;Jung, K.;Miller, D. H.;Neumeister, N.;Radburn-Smith, B. C.;Shi, X.;Shipsey, I.;Silvers, D.;Sun, J.;Svyatkovskiy, A.;Wang, F.;Xie, W.;Xu, L.;Parashar, N.;Stupak, J.;Adair, A.;Akgun, B.;Chen, Z.;Ecklund, K. M.;Geurts, F. J. M.;Guilbaud, M.;Li, W.;Michlin, B.;Northup, M.;Padley, B. P.;Redjimi, R.;Roberts, J.;Rorie, J.;Tu, Z.;Zabel, J.;Betchart, B.;Bodek, A.;de Barbaro, P.;Demina, R.;Eshaq, Y.;Ferbel, T.;Galanti, M.;Garcia-Bellido, A.;Han, J.;Harel, A.;Hindrichs, O.;Khukhunaishvili, A.;Petrillo, G.;Tan, P.;Verzetti, M.;Arora, S.;Barker, A.;Chou, J. P.;Contreras-Campana, C.;Contreras-Campana, E.;Duggan, D.;Ferencek, D.;Gershtein, Y.;Gray, R.;Halkiadakis, E.;Hidas, D.;Hughes, E.;Kaplan, S.;Kunnawalkam Elayavalli, R.;Lath, A.;Nash, K.;Panwalkar, S.;Park, M.;Salur, S.;Schnetzer, S.;Sheffield, D.;Somalwar, S.;Stone, R.;Thomas, S.;Thomassen, P.;Walker, M.;Foerster, M.;Riley, G.;Rose, K.;Spanier, S.;York, A.;Bouhali, O.;Castaneda Hernandez, A.;Dalchenko, M.;De Mattia, M.;Delgado, A.;Dildick, S.;Eusebi, R.;Gilmore, J.;Kamon, T.;Krutelyov, V.;Mueller, R.;Osipenkov, I.;Pakhotin, Y.;Patel, R.;Perloff, A.;Rose, A.;Safonov, A.;Tatarinov, A.;Ulmer, K. A.;Akchurin, N.;Cowden, C.;Damgov, J.;Dragoiu, C.;Dudero, P. R.;Faulkner, J.;Kunori, S.;Lamichhane, K.;Lee, S. W.;Libeiro, T.;Undleeb, S.;Volobouev, I.;Appelt, E.;Delannoy, A. G.;Greene, S.;Gurrola, A.;Janjam, R.;Johns, W.;Maguire, C.;Mao, Y.;Melo, A.;Ni, H.;Sheldon, P.;Snook, B.;Tuo, S.;Velkovska, J.;Xu, Q.;Arenton, M. W.;Cox, B.;Francis, B.;Goodell, J.;Hirosky, R.;Ledovskoy, A.;Li, H.;Lin, C.;Neu, C.;Sinthuprasith, T.;Sun, X.;Wang, Y.;Wolfe, E.;Wood, J.;Xia, F.;Clarke, C.;Harr, R.;Karchin, P. E.;Kottachchi Kankanamge Don, C.;Lamichhane, P.;Sturdy, J.;Belknap, D. A.;Carlsmith, D.;Cepeda, M.;Dasu, S.;Dodd, L.;Duric, S.;Friis, E.;Gomber, B.;Grothe, M.;Hall-Wilton, R.;Herndon, M.;Hervé, A.;Klabbers, P.;Lanaro, A.;Levine, A.;Long, K.;Loveless, R.;Mohapatra, A.;Ojalvo, I.;Perry, T.;Pierro, G. A.;Polese, G.;Ruggles, T.;Sarangi, T.;Savin, A.;Sharma, A.;Smith, N.;Smith, W. H.;Taylor, D.;Woods, N.
Keywords: Cms; Physics; Supersymmetry